Simulation and hardware implementation of solar energy harvester for wireless sensor networks - Hong, T.N.I. (Institute of Electrical and Electronics Engineers Inc., 2014)
Wireless Sensor Network (WSN) has emerged as a promising technology that can enable many applications such as environmental monitoring, military applications, health care monitoring, security monitoring and others. Typically, wireless sensor motes are operated using small batteries because of their size limitation. However, batteries have limited energy capacity which will be depleted eventually. A promising solution to this problem is to harvest the energy from the environment such as light, vibrations and heat. However, to maximize efficiency from poorly regulated sources such as solar panels, maximum power point tracking (MPPT) technique is required. In this paper, a simple and low cost solar energy harvester based on a chosen simple input voltage regulation loop has been simulated, followed by its hardware implementation. Results from the simulation was compared and verified through the hardware implementation. These results have shown that the incorporation of PV based solar electricity generation system have a very promising potential to enable the WSN's continuous operation. Â© 2014 IEEE.